Zinc Availability in the United States: A Statistical Analysis (2b3a4d01-2bd6-4df4-9169-077c291ec91a) - George S. Koch (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Since 1882, world zinc production has increased. In contrast, US zinc production rose until about 1915, but since then has remained nearly constant, with a slight tendency to decrease. Production from the Tri-State district, the largest early source of zinc in the US, has gone down steadily; this decline has been balanced by a growth in the rate of other districts. These changes in US production are due to economic, not geological, factors. Recent exploration has located large minable ore bodies: additional deposits will undoubtedly be found in the stratabound carbonate rock and volcanogenic environments. A statistical analysis of the exploration effort in the Middle Tennessee district indicates that new discoveries can be expected there. Thus, the US is in an early stage of the production cycle for zinc. Of major mining districts in the US, only the Tri-State is exhausted under current economic conditions; large zinc resources of low-grade material, which would repay mining at higher prices or improved technology, are known to exist in that district .